2009
DOI: 10.1007/s10528-009-9255-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evolution of 5S Ribosomal DNA Seems to Be Driven by Birth-and-Death Processes and Selection in Ensis Razor Shells (Mollusca: Bivalvia)

Abstract: A study of nucleotide sequence variation of 5S ribosomal DNA from six Ensis species revealed that several 5S ribosomal DNA variants, based on differences in their nontranscribed spacers (NTS), occur in Ensis genomes. The 5S rRNA gene was not very polymorphic, compared with the NTS region. The phylogenetic analyses performed showed a between-species clustering of 5S ribosomal DNA variants. Sequence divergence levels between variants were very large, revealing a lack of sequence homogenization. These results str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…In conclusion, the long-term evolution of 5S rDNA in Pharidae has been mainly driven by birthand-death processes and purifying selection. Nevertheless, homogenising mechanisms, such as unequal crossing-overs (favoured by the tandem organisation of 5S rDNA repeats) and gene conversions have been probably taking part, in agreement with what was previously reported on Ensis species (Vierna et al, 2009(Vierna et al, , 2010. Interestingly, recent studies in various animal groups have come to the same conclusion (Fujiwara et Linked units of 5S rDNA and U1 snDNA J Vierna et al Figure 4 Phylogenetic relationships of the 100 nucleotides upstream the 5S ribosomal DNA transcription start site of Ensis species.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In conclusion, the long-term evolution of 5S rDNA in Pharidae has been mainly driven by birthand-death processes and purifying selection. Nevertheless, homogenising mechanisms, such as unequal crossing-overs (favoured by the tandem organisation of 5S rDNA repeats) and gene conversions have been probably taking part, in agreement with what was previously reported on Ensis species (Vierna et al, 2009(Vierna et al, , 2010. Interestingly, recent studies in various animal groups have come to the same conclusion (Fujiwara et Linked units of 5S rDNA and U1 snDNA J Vierna et al Figure 4 Phylogenetic relationships of the 100 nucleotides upstream the 5S ribosomal DNA transcription start site of Ensis species.…”
Section: Discussionsupporting
confidence: 90%
“…We could suppose that divergent NTSs are located at different arrays where they have evolved independently, but we have shown that some species (S. patula and E. cultellus) have divergent NTS organised in tandem. In the same way, a few clones containing a-and d-, and a-and g-NTSs were characterised in E. directus (Vierna et al, 2009), and other studies found an intermixed organisation of 5S rDNA variants in grey mullets and E. macha (Gornung et al, 2007;Fernández-Tajes and Méndez, 2009). These findings support the idea that 5S rDNA frequently moves on within genomes (see below).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations